Canopy structure and forage mass of mixed pastures of Marandu palisadegrass and the legume Macrotyloma axillare managed under rotational stocking - Stela Soares Zamboin; Renata Helena Branco; Flavia Maria de Andrade Gimenes; Cristina Maria Pacheco Barbosa; Waldssimiler Teixeira de Mattos; Karina Batista; Gabriela Aferri; Bruna Zanini Uzan; Luciana Gerdes (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this study was to evaluate the use of grazing management strategies (GMS) in rotational stocking to improve the canopy structure in mixed pastures of Marandu palisadegrass (Brachiaria brizantha cv. Marandu) and legume Macrotyloma axillare. Treatments consisted of combinations of defoliation frequencies (pre-grazing heights of 30 and 40 cm) and intensities (post-grazing heights of 15 and 20 cm) in a 2 × 2 factorial arrangement, corresponding to four GMS: 30-15, 30-20, 40-15, and 40-20 cm, allocated to 16 experimental units (paddocks) in a completely randomized block design with four replicates. Pastures managed with 30-20, 40-15, and 40-20 cm had the highest pre-grazing legume masses (P = 0.0378), but for all GSM, there was a reduction of legume in the forage mass over time (P<0.0001). In Summer 1, legume was observed in the upper strata of the pre-grazing profile for all GMS, but in Summer 2, it was only detected in the 20-25 cm stratum of the 30-20 and 40-20 cm GMS. Pastures managed with 30-20 cm had a high pre-grazing bulk density of total forage, grass, and legume leaf (P<0.05), and a high post-grazing grass leaf mass and bulk density. The highest pre- and post-grazing stem mass and bulk density occurred in pastures with a pre-grazing height of 40 cm (P<0.05). The lower defoliation frequencies (pre-grazing height of 40 cm) had no benefits for the canopy structure. Among the GMS evaluated, a pre-grazing height of 30 cm and a post-grazing height of 20 cm resulted in the most suitable canopy structure for grazing.